The Direct Costs of Dravet's Syndrome before and after Diagnosis Assessment - Česká, Katarína; Český, Lukáš; Ošlejšková, Hana; Aulická, Štefánia (Neuropediatrics, 2020)
The objective of this study was to estimate the direct cost before and after diagnosis assessment in patients with Dravet's syndrome (DS). The basis of the economic study was to calculate the costs of health care before and after diagnosis of DS. We retrospectively evaluated all SCN1A positive patients with phenotype of DS treated in our hospital. Statistical analyses were performed by IBM SPSS Statistics 24.0 software. After the diagnosis of DS, there was a significant decline of health care costs (−85.6%) an average of €29.4 ± 26.1 monthly per patient. We estimated the monthly costs at €204.5 ± 167 (median: €193.9, range: €35.5–534.4) per patient before DS diagnosis. The major cost was for hospitalization in neurological department: €43.3 ± 52 (median: €21.9, range: €9.5–179.4) per patient. Minimal cost per patient per months before DS diagnosis was cost of psychological testing/care and complementary rehabilitation (0.13 and 0.6% of total cost). After DS diagnosis, the major cost was focused on nonhospitalization care of patients (64.8%), minimal (€0) for genetic testing and major for outpatient care (18%, mean: €5.3, median: €7). DS results in essential health care utilization and high financial burden before diagnosis elucidation caused by repeated hospitalization and extensive diagnostics tests of “epileptic encephalopathy of unknown etiology.” The results of this study point out that early assessment of the diagnosis leads to significant decrease of the financial costs because of adequate therapeutic management and exclusion of redundant diagnostic testing after elucidation of correct diagnosis.
Keywords: epilepsy; Dravet's syndrome; economic study; costs